A Qualitative Investigation into Components of Patient Safety Organizational Culture in the Medical Education Centers: A Medical Errors Management Approach - Rohangiz Mohamadi Khoshoui‌; Shayesteh Salehi; Narges Saeedian (Kerman University of Medical Sciences, 2020)
Introduction: The patient safety is a subset of organizational culture and is defined as a set of individual and organizational priorities, values, attitudes and behaviors which look for minimizing errors and damages arising from the process of patient treatment.  This study seeks to describe the experiences of patients and their companions about the patient safety organizational culture and medical errors management. Methods: This qualitative study was conducted in the health and medical education centers affiliated with Isfahan University of Medical Sciences in 2017. A total of 15 patients and companions receiving health services in medical education centers were selected using purposive sampling and in-depth interviews were conducted with the participants. Conventional qualitative content analysis was used to analyze the data. Results: 186 initial codes, 23 sub-subcategories and 6 main themes were extracted from the data which are as follows: culture of errors acceptance vs. non-acceptance, culture of disclosing vs. hiding errors, psychological and physical consequences and financial burden of medical errors, learning from errors, the culture of patient participation and training, developing the culture of safety and all-inclusive quality improvement. Conclusion: The results of the present study indicate a vast array of culture of non-acceptance vs. acceptance of errors and disclosing vs. hiding errors. Thus, it is imperative for the organization's senior managers to make corrective interventions so as to maintain and promote the culture of learning from errors and patient education and participation in the process of their treatment and ultimately the culture of safety and all-inclusive quality improvement.